Disseminated Infections with Talaromyces marneffei in Non-AIDS Patients Given Monoclonal Antibodies against CD20 and Kinase Inhibitors - Jasper F.W. Chan; Thomas S.Y. Chan; Harinder Gill; Frank Y.F. Lam; Nigel J. Trendell-Smith; Siddharth Sridhar; Herman Tse; Susanna K.P. Lau; Ivan F.N. Hung; Patrick C.Y. Woo; Kwok-Yung Yuen (Emerging Infectious Diseases, 2015)
Infections with the fungus Talaromyces (formerly Penicillium) marneffei are rare in patients who do not have AIDS. We report disseminated T. marneffei infection in 4 hematology patients without AIDS who received targeted therapy with monoclonal antibodies against CD20 or kinase inhibitors during the past 2 years. Clinicians should be aware of this emerging complication, especially in patients from disease-endemic regions.